Reconstruction of Head and Neck Mucormycosis: A Literature Review and Own Experience in Immediate Reconstruction - Palacios, Julio Juarez; Hanson, Erik Viana; Rendon, Marco Aurelio Medina; Infante, Raúl-Saldaña López (Journal of Reconstructive Microsurgery Open, 2019)
Background Mucormycosis is a rare invasive and fatal fungal infection. A prompt diagnosis is the most critical aspect for an improved patient outcome. Along with antifungal therapy, radical surgical debridement must be done expeditiously to eradicate this fungus. In this article, we evaluated the feasibility of immediate reconstruction after surgical debridement.Methods A retrospective study was performed at Hospital Regional de Alta Especialidad de Ixtapaluca, Estado de México, Mexico, between June 2017 and June 2018. Five patients, three males and two females, with a mean age of 39 years were presented in addition to a literature review based on MEDLINE, Google Scholar, PubMed Central, and Embase platforms until June 2018.Results From our presented series, all five flaps survived and showed no evidence of mucormycosis recurrence or flap loss. In the literature review, we collected 16 cases from 14 different publications of individuals with head and neck mucormycosis. Reconstruction was made with a free (12 cases) or pedicled flap (four cases). Eleven males and five females with a mean patient age of 33.0 years were studied. Only two authors described an early or immediate reconstruction. The average time of the delayed reconstruction after surgical debridement was 16.7 weeks.Conclusion After aggressive surgical resection, immediate reconstruction can be done safely based on clinical criteria and as long as there is no evidence of hyphae invasion on wound edges in the intraoperative pathology examination.
Keywords: mucormycosis reconstruction; zygomycosis reconstruction; mucormycosis flap